Optimal Use of Perampanel in Asian Patients with Epilepsy: Expert Opinion - Chinvarun Y; Huang CW; Wu Y; Lee HF; Likasitwattanakul S; Ding J; Yamamoto T (Dove Medical Press, 2021)
Yotin Chinvarun,1 Chin-Wei Huang,2 Ye Wu,3 Hsiu-Fen Lee,4 Surachai Likasitwattanakul,5 Jing Ding,6 Takamichi Yamamoto7 1Department of Neurology, Phramongkutklao Royal Army Hospital and Medical College, Bangkok, Thailand; 2Department of Neurology, National Cheng Kung University Hospital College of Medicine, National Cheng Kung University, Tainan, Taiwan; 3Department of Pediatrics, Peking University First Hospital, Beijing, People's Republic of China; 4Division of Pediatric Neurology, Children's Medical Center, Taichung Veterans General Hospital, Taichung, Taiwan; 5Division of Neurology, Department of Pediatrics, Faculty of Medicine, Siriraj Hospital, Mahidol University, Bangkok, Thailand; 6Department of Neurology, Zhongshan Hospital, Fudan University, Shanghai, People's Republic of China; 7Department of Neurosurgery, Comprehensive Epilepsy Center, Seirei Hamamatsu General Hospital, Hamamatsu, JapanCorrespondence: Takamichi YamamotoDepartment of Neurosurgery, Comprehensive Epilepsy Center, Seirei Hamamatsu General Hospital, 2-12-12 Sumiyoshi, Hamamatsu, Shizuoka, 430-8558, JapanTel +81 53 474 2222Fax +81 53 474 3094Email taka-yamamd@sis.seirei.or.jpAbstract: Perampanel is a once-daily, first-in-class AMPA receptor antagonist approved for the treatment of epilepsy and exhibits broad-spectrum efficacy in a range of seizure types when used as both monotherapy and adjunctive therapy. Clinical studies and real-world evidence have demonstrated the advantages of initiating perampanel at low doses and utilizing a slow titration strategy. Initiating perampanel at an early stage has also been shown to be associated with better patient outcomes. However, the optimal use and place of perampanel in clinical practice has not yet been clearly defined for the Asian patient population. Use of perampanel in clinical practice varies markedly across the Asia region because of variation in knowledge, attitudes, and practice. There is currently no specific guidance on best practices for prescribing perampanel in Asian patients or how to optimize treatment strategies to maximize adherence. A group of epilepsy experts attended a virtual meeting in September 2020 to discuss their experience with using perampanel in the Asian practice setting, including their views regarding appropriate patient populations, optimal starting and maintenance doses, optimal titration regimens, key barriers to adherence, and prevention and management of adverse events. This article summarizes key clinical and real-world evidence for perampanel and consolidates the experts' opinions on optimization of perampanel prescribing and adherence in real-world practice, providing practical strategies for clinicians to implement to improve outcomes for people with epilepsy in Asia.Keywords: perampanel, epilepsy, real-world experience, Asia